Kesegaran Ikan Nila Berdasarkan Uji Organoleptik - Ayu Anggraeni Cahya Pitaloka (Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2021)
Fish is an animal whose freshness must be maintained, from catching to processing so that it is not easily contaminated by microorganisms and is not easily damaged, this is because fish contains high levels of water and protein. Improper fishing and storage of fish can cause fish to become bruised and contaminated by microorganisms